2020
DOI: 10.1297/cpe.29.111
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic hypoglycemia in a child with common variable immunodeficiency: Deficient anterior pituitary with variable immune deficiency (DAVID) syndrome

Abstract: Deficient anterior pituitary with variable immune deficiency (DAVID) syndrome is a rare condition characterized by symptomatic ACTH deficiency and primary hypogammaglobulinemia, caused by pathogenic variants of the nuclear factor kappa-B subunit 2 (NF-κB2) gene. We report the case of a 9-yr-old boy diagnosed with common variable immunodeficiency at the age of 3, who is under monthly intravenous immunoglobulin. The patient was admitted twice to the pediatric emergency service at the age of 9 due to symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Other concomitant endocrinopathies (growth hormone deficiency, hypothyroidism, and diabetes insipidus) have also been described [11, 13, 1822], but those were not found in our patient. The hypoplastic pituitary identified in our patient was also reported in 6 other patients [13, 15, 16, 21, 23, 24], but it is not a characteristic feature as the studies in Lym1 mouse models carrying pathogenic mutations in the NF-κB2 gene also show normal pituitary anatomy, hypothesizing that NF-κB2 pathogenic mutations have inconsistent effects on the development of the hypophysis [9]. To summarise, DAVID syndrome widened our approach towards the aetiology of hypoglycaemia and un-curtained this peculiar yet rare association.…”
Section: Discussionsupporting
confidence: 88%
“…Other concomitant endocrinopathies (growth hormone deficiency, hypothyroidism, and diabetes insipidus) have also been described [11, 13, 1822], but those were not found in our patient. The hypoplastic pituitary identified in our patient was also reported in 6 other patients [13, 15, 16, 21, 23, 24], but it is not a characteristic feature as the studies in Lym1 mouse models carrying pathogenic mutations in the NF-κB2 gene also show normal pituitary anatomy, hypothesizing that NF-κB2 pathogenic mutations have inconsistent effects on the development of the hypophysis [9]. To summarise, DAVID syndrome widened our approach towards the aetiology of hypoglycaemia and un-curtained this peculiar yet rare association.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with previous studies that demonstrated the presence of autoimmune hormonal dysfunctions, including hypothyroidism, hypogonadism, and adrenal insufficiency in adult patients with CVID ( 13 ). In pediatric patients presenting with CVID and adrenocorticotropin deficiency, the suspicion of DAVID syndrome (deficient anterior pituitary with variable immune deficiency) due to pathogenic variants in the NF- κ B2 (nuclear factor kappa B2) gene should be raised ( 32 , 33 ). Other autoimmune disorders included cytopenias, most frequently AIHA in three of 18 patients with CVID and autoimmunity, and autoimmune thrombocytopenic purpura (ITP), autoimmune neutropenia (AIN), leucopenia, and pancytopenia, which were present in single cases.…”
Section: Discussionmentioning
confidence: 99%
“…1A, Table SI). The recurrence of this variant probably reflects the existence of a mutational hotspot, as opposed to a founder effect, because this variant was previously detected in patients from nine different countries and was shown to have occurred de novo in six patients [79][80][81][82][83][84] . The other 12 patients were heterozygous for NFKB2 variants in the Rel homology domain (RHD) (n=3 from 3 kindreds; pLOF, n=2 and missense, n=1), or the ankyrin repeat domain (ARD) (pLOF, n=6 patients from 3 kindreds, and missense, n=3 from 3) (Fig.…”
Section: A Cohort Of Patients With Inborn Errors Of the Alternative N...mentioning
confidence: 99%